2021
DOI: 10.3920/wmj2020.2664
|View full text |Cite
|
Sign up to set email alerts
|

Developments in mycotoxin analysis: an update for 2019-2020

Abstract: This review summarises developments on the analysis of various matrices for mycotoxins published in the period from mid-2019 to mid-2020. Notable developments in all aspects of mycotoxin analysis, from sampling and quality assurance/quality control of analytical results, to the various detection and quantitation technologies ranging from single mycotoxin biosensors to comprehensive instrumental methods are presented and discussed. Aside from sampling and quality control, discussion of this past year’s developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 91 publications
0
42
0
Order By: Relevance
“…From an analytical-chemical point of view, it is relevant to observe differences in ionization of the compounds (see Figure 3 ), so a sum value with either or both toxins, as standards will lead to inaccurate quantification when there is no chromatographical separation. Multi-mycotoxin methods based on LC-MS/MS are widely used nowadays [ 11 , 12 ], but remain a compromise in various aspects in order to “squeeze in” a multitude of analytes in a single method. In case accurate quantification of 3ADON and 15ADON is warranted, methods not resolving the compounds cannot be recommended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From an analytical-chemical point of view, it is relevant to observe differences in ionization of the compounds (see Figure 3 ), so a sum value with either or both toxins, as standards will lead to inaccurate quantification when there is no chromatographical separation. Multi-mycotoxin methods based on LC-MS/MS are widely used nowadays [ 11 , 12 ], but remain a compromise in various aspects in order to “squeeze in” a multitude of analytes in a single method. In case accurate quantification of 3ADON and 15ADON is warranted, methods not resolving the compounds cannot be recommended.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the European Food Safety Authority proposed a group tolerable daily intake value of 1 µg/kg bodyweight for the sum of the four compounds [10]. The most popular technique to determine mycotoxins in food nowadays [11,12] is liquid chromatography coupled to mass spectrometry (LC-MS). Typically reversed phase chromatography on a C-18 column is used to separate mycotoxins of different polarities, before they are charged during electrospray ionization and subsequently analyzed with MS [13].…”
Section: Introductionmentioning
confidence: 99%
“…Mycotoxins or fungal contaminants are also major biological hazards, while few research papers on MIP-based electrochemical sensors for mycotoxins detection have been reported. The development of an accurate analytical method for the detection of mycotoxins is highly needed to satisfy food safety requirements [ 123 , 124 ]. Recently, Huang et al [ 115 ] applied thionine as both functional monomer and signal indicator to form an electrochemical sensor for the detection of patulin that is produced by Aspergillus , Penicillium , and Byssochlamys species.…”
Section: Mip-based Electrochemical Sensorsmentioning
confidence: 99%
“…However, this correlation is often moderate at best (Buerstmayr et al, 2004 ; Choo et al, 2004 ; He et al, 2015 ; Huang et al, 2018 ; Tucker et al, 2019 ). Mycotoxin quantification is highly technical, where sampling protocols, quality controls and choice of analytical technologies are all implicated as important factors (Tittlemier et al, 2021 ). Analytical chemistries are expensive and labor requirements for harvest and processing grains are substantial.…”
Section: Introductionmentioning
confidence: 99%